2014
DOI: 10.1002/jbmr.2342
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of Bone SOST, Its mRNA, and Serum Sclerostin Levels Correlate Strongly With Fracture Risk in Postmenopausal Women

Abstract: Inhibition of sclerostin, a glycoprotein secreted by osteocytes, offers a new therapeutic paradigm for treatment of osteoporosis (OP) through its critical role as Wnt/catenin signaling regulator. This study describes the epigenetic regulation of SOST expression in bone biopsies of postmenopausal women. We correlated serum sclerostin to bone mineral density (BMD), fractures, and bone remodeling parameters, and related these findings to epigenetic and genetic disease mechanisms. Serum sclerostin and bone remodel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
67
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 39 publications
5
67
1
Order By: Relevance
“…For example, increased methylation of the SOST promoter has been reported in bone samples of patients with osteoporosis. 51 As sclerostin is an antianabolic factor, this finding may be counterintuitive; yet, it is in line with studies showing reduced SOST expression in osteoporosis. 51,71 Although the involved mechanisms are still unclear, it has been suggested that those changes are a compensatory response, rather than a driver of the bone loss.…”
Section: Direction Of Effects and Causationsupporting
confidence: 68%
See 1 more Smart Citation
“…For example, increased methylation of the SOST promoter has been reported in bone samples of patients with osteoporosis. 51 As sclerostin is an antianabolic factor, this finding may be counterintuitive; yet, it is in line with studies showing reduced SOST expression in osteoporosis. 51,71 Although the involved mechanisms are still unclear, it has been suggested that those changes are a compensatory response, rather than a driver of the bone loss.…”
Section: Direction Of Effects and Causationsupporting
confidence: 68%
“…These studies have small costs, but they miss information from the vast majority of the genome. More recently, Reppe 51 focused in the analysis of the methylation of the SOST promoter (the gene encoding sclerostin) and its association with BMD.…”
Section: Tissuementioning
confidence: 99%
“…It is considered as a compensatory, counteracting mechanism, which lowers sclerostin production and reduces inhibition of Wnt signaling in an attempt to promote bone formation. 38 However, serum sclerostin is unaffected by menopausal status or increase in age, perhaps due to kidney aging accompanied by deterioration of their excretory and biodegradation functions. It is generally accepted that sclerostin in postmenopausal women reflects bone mineral density.…”
mentioning
confidence: 99%
“…Aside from the group of rare genetic diseases, the observable variability of serum sclerostin levels affects BMD of both cortical and cancellous bone in the general population. The molecular effect of sclerostin levels and BMD were studied by Reppe et al 30 They showed that the genetic and epigenetic changes in SOST influence its mRNA expression in bone and serum sclerostin levels in postmenopausal women. Serum sclerostin and bone SOST mRNA expression correlated positively with age-adjusted and BMI-adjusted total hip BMD (r = 0.47) and inversely to serum bone turnover markers.…”
mentioning
confidence: 99%
See 1 more Smart Citation